Influence ratio of water and oil phases of emulsions on viscosity, particle size and muddy turbidity of products - Lugovska, Oksana; Sidor, Vasyl (My University, 2014)
The paper systematically describes the basic theoretical information about the improvements in the production of emulsions. We consider the theory of a stable emulsion system, namely the particular use of raw materials and their properties analyzed the conditions necessary for the process of homogenization. And based on this, a large number of existing theories determined the most effective, which is used for the production of emulsions.Much attention is paid to the use of different stabilizers receipt of test data required for the calculation formulas finished products, and technological design process of emulsions. To assign these methods using two stabilizers: resin acacia and modified starch, which when used for stability during storage of emulsions yield different results. Of great importance for the stability of these products is the size of the particles. The diameter of the emulsion depends on a process of manufacturing technology.More detail the process of homogenization of emulsions. For the features of this process are a few examples that will visually see the results emulsion stability during storage.Based on the processed foreign sources give modern technology and types of equipment for the homogenization process, with reference to the drawings, which will assimilate the information produced. We consider the design features of these devices, their advantages and disadvantages.
Keywords: stabilizer; emulsion; particle size; phase; stability; стабілізатор; емульсії; розмір частинок; фази; стабільність; стабилизатор; размер частиц; эмульсии; фазы; стабильность; кафедра експертизи харчових продуктів